Real-Time Surveys Reveal Important Safety Risks During Interhospital Care Transitions for Neurologic Emergencies. (January 2019) - Sather, John; Rothenberg, Craig; Finn, Emily B.; Sheth, Kevin N.; Matouk, Charles; Pham, Laura; Parwani, Vivek; Ulrich, Andrew; Venkatesh, Arjun K.
Critically ill patients may be exposed to unique safety threats as a result of the complexity of interhospital and intrahospital transitions involving the emergency department (ED). Real-time surveys were administered to clinicians in the ED and neuroscience intensive care unit of a tertiary health care system to assess perceptions of handoff safety and quality in transitions involving critically ill neurologic patients. In all, 115 clinical surveys were conducted among 26 patient transfers. Among all clinician types, 1 in 5 respondents felt the handoff process was inadequate. Risks to patient safety during the transfer process were reported by 1 in 3 of respondents. Perceived risks were reported more frequently by nurses (44%) than physicians/advanced practice providers (28%). Real-time survey methodology appears to be a feasible and valuable, albeit resource intensive, tool to identify safety risks, expose barriers to communication, and reveal challenges not captured by traditional approaches to inform multidisciplinary quality improvement efforts.